Exploring staff and children satisfaction on environmental qualities of rehabilitation centers for children in conflict with the law in Davao City - Solidarios, Nikka Louie Marie C.; Puso, Mark Ndsy L. (2020)
The undeniable importance of rehabilitation centers for children in conflict with the law in the society promotes the need to guarantee that these centers support every rehabilitation service needed by the children. Using the Quality-care Characteristics Theory from the Research Center of Harvard University, Service Quality Perception of users by Fransesc Medina-Mirapeix PT, Ph.D., and Accident Causation Theory by H.W. Heinrich. This research analyzed four characteristics of three rehabilitation centers for children in conflict with the law in Davao city: ageappropriateness, safety, ability to support responsive relationship, and encourage learning, and physical activities. The study aims to collect data that could help determine the centers? strengths and weaknesses in each characteristic. Through qualitative and quantitative research, the Regional Rehabilitation Center for Youth, Children?s Village Bahay Pag-asa, and Group Home for Girls and Women were studied. Descriptive numerical measures and triangulation assessed the data and results. These methods were used to enrich the reliability of the collected data from the study areas. The analysis of the data was used as a basis to formulate the architectural guidelines for the proposed coeducational rehabilitation center for children in conflict with the law in Davao city
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020